PROFIL NUMBER SENSE SISWA SMP DALAM MEMECAHKAN MASALAH MATEMATIKA BERDASARKAN JENIS KELAMIN - Arion Palandu; Muh. Rizal (Universitas Tadulako, 2022)
This study aims to obtain a description of the number sense profile of male and female students with high mathematical abilities in solving mathematics problems. This subject of this study were two grade VII students of SMPN 1 Palu in the odd semester of the 2019/2020. Two students selected as research subject consisted of a male student with high math ability and a female student with high math ability. The number sense data of the two subjects were obtained through problem-solving tests and unstructured interviews which were then analyzed qualitatively. The results showed that male student with high math ability had good number sense in solving math problems by utilizing their understanding of numbers. Meanwhile, female students with high math ability use simpler ways to solve problems quickly than male. The results showed that female students had a good number sense in solving math problems by utilizing their understanding of numbers.